2016
DOI: 10.1109/tns.2016.2535328
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Production of Photonic Crystals on Scintillators

Abstract: Abstract-Heavy inorganic scintillator based detectors are used in various applications. You can find them in high energy physics as well as in nuclear medical imaging systems but also in homeland security radiation monitoring devices. In all these different detectors, light is produced in the scintillator and has to be transported towards a photodetector. The standard optical coupling of such a detector suffers from an inefficient light extraction towards the photodetector due to the high index of refraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As demonstrated by earlier work (Levin 2002), measured light output for side readout of long and narrow scintillation crystals is substantially improved compared to the case where a crystal is coupled to a photosensor on its narrow end (figure 8(a)). For context, consider that in recent years significant effort has been put forth to improve LCE with end-coupled scintillation crystals by exploiting photonic crystal techniques (Knapitsch and Lecoq 2014), and simulated gain in LCE for optimized nanoimprinted structures predict 15%-30% improvement compared to a polished exit coupled to a sensor with an optical glue (Knapitsch et al 2016). In section 3.1 we showed that >50% improvement in LCE can already be achieved with the side readout orientation of a 20 mm length crystal, compared to end readout of a crystal with the same length.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by earlier work (Levin 2002), measured light output for side readout of long and narrow scintillation crystals is substantially improved compared to the case where a crystal is coupled to a photosensor on its narrow end (figure 8(a)). For context, consider that in recent years significant effort has been put forth to improve LCE with end-coupled scintillation crystals by exploiting photonic crystal techniques (Knapitsch and Lecoq 2014), and simulated gain in LCE for optimized nanoimprinted structures predict 15%-30% improvement compared to a polished exit coupled to a sensor with an optical glue (Knapitsch et al 2016). In section 3.1 we showed that >50% improvement in LCE can already be achieved with the side readout orientation of a 20 mm length crystal, compared to end readout of a crystal with the same length.…”
Section: Discussionmentioning
confidence: 99%
“…Notice that for the lower refractive index, the optimal periodicity is shifted to higher values (up to 1.7 µm). On the same line, our collaboration published a work [64] that identified the hybrid structure as a convenient option for large-scale production of PhC slabs. The expected gain in LY for a PhC slab of hexagonally-placed cones of TiO 2 (RI = 2.5), 700 nm period and 1.5 µm height, applied to an 10 × 10 × 10 mm 3 LYSO Teflon wrapped and optically coupled to the PMT is 1.3.…”
Section: Hybrid Phc Slabs: Diffraction and Index Matchingmentioning
confidence: 99%
“…This is a relatively simple method to obtain a mono-layer of nano-spheres that will arrange themselves in a hexagonal lattice. Afterwards, the layer is treated with a plasma, thereby shrinking the nano-spheres to the desired dimension [64,65].…”
Section: Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Lijing Zhang, Jie Wang, Shengyang Tao,* Chong Geng, and Qingfeng Yan DOI: 10.1002/adom.201701344 of light due to the existence of a photonic bandgap (PBG) and have been widely used in ultralow reflection solar cells, [6] LED light output, [7] light extraction from scintillation materials, [8] and FL enhancement. [9][10][11][12][13] Studies have shown that light propagates near the PBG will be at reduced group velocity owing to resonant Bragg scattering, which can enhance optical gain leading to stimulated emission and amplify the excitation of incident light.…”
Section: Universal Fluorescence Enhancement Substrate Based On Multipmentioning
confidence: 99%